Faktor-Faktor yang Mempengaruhi Pinjaman Luar Negeri serta Imbasnya terhadap APBN - Saleh, Samsubar (Unisia, 2012)
The research and study cover a theoretical discussion and empirical study on factors affecting the Indonesian Government’s foreign debt and their impact on the State Revenues and Expenditures Budget (APBN) based on annual data from 1970 to 2008. The research employs the Error Correction Model (ECM) approach by applying the Ordinary Least Square (OLS) method. The research results indicate that within a long-term period, there was a balance between changes in the Indonesian Government’s foreign debts and macro-economic variables, i.e. budget deficit, exchange rate, export, GNP level, and dummy variables for the 1997 economic crisis, despite the fact that the budget deficit variable did not significantly affect the Indonesian Government’s foreign debts within the observed period. On the other hand, within a short-term period changes in the Indonesian Government’s foreign debts were affected significantly by dummy variables for the 1997 economic crisis and the ECT variable. Within such a period, the budget deficit, exchange rate, export, and GNP level variables did not significantly affect by the Indonesian Government’s foreign debts. Thus, it could be concluded that the Indonesian Government’s foreign debts tended to respond to changes occurring in macro-economic variables, especially export, exchange rate, economic growth, and condition of foreign debts post-1997 economic crisis. Keywords: foreign debt, budget, balance, macro-economic.